Cardiorespiratory variables of the six-minute walking test of women submitted to bariatric surgery. - Peixoto-Souza, Fabiana Sobral; Baltieri, Letícia; Costa, Dirceu; Piconi-Mendes, Camila; Rasera- -Junior, Irineu; Barbalho-Moulim, Marcela Cangussu; Pazzianotto-Forti, Eli Maria (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: It’s known that bariatric surgery provides an improvement in the functional capacity and cardiorespiratory performance. However, most of these studies are limited to the distance walked during the 6MWT as a function of the functional capacity. Objective: The goal of this study was to evaluate the functional capacity and cardiorespiratory responses of women with morbid obesity, applying the six-minute walk test before and 6 months after bariatric surgery. Method: Prospective and observational study in which 14 women with morbid obesity submitted to Roux-en-Y gastric bypass derivation were studied. The volunteers performed made the six-minute walking test (6MWT) before and six months after surgery. The distance walked and the blood pressure were registered as well as the subjective sensation of dyspnea and exhaustion of the lower limbs. In addition, the heart rate, oxygen saturation and breathing rate were registered at the beginning, during the end of the 6MWT. Results: An increase in the distance walked was observed 6 months postsurgery (588.92 ± 34.81m) as compared to the preoperative distance (516.28 ± 50.91m). Regarding to the cardiorespiratory variables, which included the heart rate (HR), blood pressure (BP), peripheral oxygen saturation (SatO2), respiratory rate (RR) and sensation of dyspnea, there was a decrease in the systolic and diastolic blood pressures during the recovery period of the 6MWT. There was no statistical difference in the other variables analyzed. Conclusion: the bariatric surgery and the following weight loss provided improvements in the functional capacity and blood pressure values during recovery from the exercise.